Increased risk of sleep-related movement disorder in patients with Helicobacter pylori infection: A nationwide population-based study - Sung, Yueh-Feng; Yin, Jiu-Haw; Lee, Kuang-Heng; Tsai, Chia-Lin; Lin, Yu-Kai; Chen, Shao-Yuan; Chung, Chi-Hsiang; Chien, Wu-Chien; Lee, Jiunn-Tay; Chou, Chung-Hsing (Frontiers in Neurology, 2022)
Background and Purpose: Evidence increasingly suggests that Helicobacter pylori infection (HPI) is associated with movement disorders such as Parkinson’s disease (PD). However, the relationship between HPI and sleep-related movement disorders (SRMD) remains unknown. This nationwide population-based study tried to demonstrate whether HPI patients have a higher risk to develop SRMD in a general adult population. Methods: The study cohort enrolled 9,393 patients who were initially diagnosed as HPI between 2000 and 2013. 37,572 age- and sex-matched patients without prior HPI were selected as the reference. A Cox proportional hazard regression analysis was performed for multivariate adjustment. Results: Patients with HPI had a higher risk to develop SRMD (adjusted hazard ratio [HR] = 2.18, 95% confidence interval [CI] = 1.26–3.82, p<0.01). HPI patients aged ≥65 years exhibited the highest risk (HR = 3.01, 95% CI = 1.90–5.30, p<0.001), followed by patients aged 45 to 64 years (HR = 1.69, 95% CI = 1.26–2.90, p<0.01) and <45 years (HR = 1.49, 95% CI = 1.12–2.49, p<0.01). Patients were most likely to develop SRMD 5 years or more after diagnosis of HPI (HR = 3.33, 95% CI = 1.97–5.89, p<0.001). The increased risk of SRMD in HPI males (HR = 2.73, 95% CI = 1.53–4.79, p<0.001) was greater than females (HR = 1.14, 95% CI = 1.04–1.65, p<0.05). Conclusions: Patients with HPI were associated with an increased risk for SRMD, with a higher risk in males, aged ≥65 years, and diagnosed for more than 5 years.